Superiority of Spacer/Mask Topical Anesthetic Compared with Conventional Spray and Gargle Method for Fibreoptic Bronchoscopy - RC Balkissoon; L Clelland; L Whitehead; MT Newhouse (Canadian Respiratory Journal)
OBJECTIVE: To compare the safety and efficacy of a new spacer-oral nasal mask device with those of the standard needle nozzle spray method for the delivery of aerosolized lidocaine to the upper airway for pre-bronchoscopic anaesthesia in a tertiary care hospital.